Treatment of palm oil mill effluent by poly(L-lactic acid)-poly(ethylene glycol)/silica membrane - Fatimah Zahrah Mohd Kamil,; Norilyani Izzati Hasanuddin,; Rizafizah Othaman,; Farah Hannan Anuar, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Biodegradable membrane technology has received an increasing interest in many fields of applications exclusively to preserve the earth. A renewable polymer such as poly(L-lactic acid) (PLLA) often being introduced with reinforcement material to improve the characteristics of membranes itself. Herein, this study highlights the development of membrane from poly(L-lactic acid)-poly(ethylene glycol) (PLLA-PEG) copolymer with silica (SiO2 ) in the treatment of palm oil mill effluent (POME) wastewater. We hypothesized that the incorporation of SiO2 as a nanofiller promoted PLLA-PEG/ SiO2 membrane to have a porous and higher number of pores on the membrane surface. Therefore, the effect of silica amount added in the PLLA-PEG copolymer membrane was also investigated and examined by using Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDX). Based on FTIR analysis, the presence of the urethane (-NHCOO-) functional group indicated the formation of PLLAPEG copolymer and SEM micrographs showed porous surface on the membranes with increasing pores size in a favor of SiO2 amount added. Also, the surface wettability of membranes was evaluated through water contact angle which render hydrophilic characteristics. These membranes were subsequently applied for POME filtration where the test resulted in significant discolouration of POME. Furthermore, the high percentage removal efficiency of biochemical oxygen demand (BOD), chemical oxygen demand (COD) and total suspended solid (TSS) up to 99.5% empowers the treated POME wastewater to be within the range set by the Malaysian Department of the Environment.